Reactive oxygen species drove red lineage phytoplankton to displace green lineage phytoplankton during the Mesozoic - Yuxi Zhao; Man Tong; Li Tian; Genming Luo; Ping Li; Haijun Song; Zhong-Qiang Chen; Shucheng Xie; Andreas Kappler; Songhu Yuan (Proceedings of the National Academy of Sciences, 2026)
The great phytoplanktonic shift from green to red plastid lineage dominance in the early Mesozoic marks a primary producer revolution in marine ecosystems, facilitating the rise of modern ecosystems and impacting global carbon cycling and energy flows. The causes driving this evolutionary transition have been attributed to the changes in essential nutrients and the environmental crises of the Permian–Triassic mass extinction. Nonetheless, the underlying mechanisms driving this transition remain poorly understood. Here, we integrated culture experiments, molecular and physiological analyses, big data analysis, and phylogenomic dating analyses to uncover how environmental stresses influence algal physiology, thereby altering their evolutionary trajectories. We find that environmental and endogenous reactive oxygen species (ROS) collaboratively shape phytoplanktonic responses. The structural characteristics of red lineage phytoplankton enhance resistance to environmental ROS, facilitating physiological strategies that minimize endogenous ROS accumulation, thereby driving more adaptive evolutionary trajectories under environmental stresses in the early Mesozoic. The alignment of the turnover in diversification dynamics between the two lineages with paleoenvironmental shifts that triggered increased ROS production supports the role of ROS in driving this evolutionary transition. Our findings highlight ROS as a key underlying factor driving phytoplankton evolution, providing predictive insights into major biota–environment coevolutions throughout Earth’s history.